Intestinal metastasis from carcinoma cervix: An (un) common occurrence in a common cancer. A series of five cases from a single institution - Radhika Narayan (Indian Journal of Pathology and Microbiology, 2022)
Carcinoma cervix usually spreads directly to contiguous structures, such as the vagina, urinary bladder, ureter, and rectum. Intestinal metastasis from cervical cancer is very uncommon and accounts for less than 4% of cases and to date, 24 cases have been reported in Medical literature. These may be asymptomatic or present with features of intestinal obstruction, bowel wall perforation, and mimic acute abdomen. Intestinal metastasis is a late occurrence and carries a poor prognosis, hence a high index of suspicion with prompt diagnosis and management is essential. We report a series of five patients with squamous cell carcinoma (SCC) of the cervix with intestinal metastasis diagnosed in our hospital.